Oil Contamination Detection System (OCDS) - Mohd Hafiz, Fazalul Rahiman; Abd. Haqi, Ibrahim; Mohd Taufik, Jusoh@Tajudin; Soh, Ping Jack; Ahmad Firdaus, Ahmad Zaidi (Malaysian Invention and Design Society (MINDS), 2010)
Mohd Hafiz Fazalul and his team won bronze at ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.